An improved human skin explant culture method for testing and assessing personal care products. (6th January 2023) - Zhou, Linli; Ji, Wei; Dicolandrea, Teresa; Finlay, Deborah; Supp, Dorothy; Boyce, Steven; Wei, Karl; Kadekaro, Ana Luisa; Zhang, Yuhang
Abstract: Background: Cultured human skin models have been widely used in the evaluation of dermato‐cosmetic products as alternatives to animal testing and expensive clinical testing. The most common in vitro skin culture approach is to maintain skin biopsies in an airlifted condition at the interface of the supporting culture medium and the air phase. This type of ex vivo skin explant culture is not, however, adequate for the testing of cleansing products, such as shampoos and body washes. One major deficiency is that cleansing products would not remain confined on top of the epidermis and have a high chance of running off toward the dermal side, thus compromising the experimental procedure and data interpretation. Materials and Methods: Here, we describe an improved ex vivo method for culturing full‐thickness human skin for the effective testing and evaluation of skin care products by topical application. Results: This newly developed ex vivo human skin culture method has the ability to maintain healthy skin tissues for up to 14 days in culture. Importantly, the model provides a quick and safe way to evaluate skin care products at different time points after single or repetitive topical applications using a combined regimen of leave‐on and wash‐off. We found that the results obtained using the new skin culture method are reproducible and consistent with the data collected from clinical testing. Conclusion: Our new ex vivo skin explant method offers a highly efficient and cost‐effective system for the evaluation and testing of a variety of personal care products and new formulations.